Liver stiffness in Fontan patients: the effect of respiration and food intake - Braun, Annabell; Mühlberg, Richard; Fischer, Marcus; Haas, Nikolaus A.; Meyer, Zora (Frontiers in Medicine, 2023)
Objectives: Fontan-associated liver disease is a well known long-term consequence in Fontan patients, due to the chronically increased Central Venous Pressure after Fontan palliation. It carries an increased risk of liver cirrhosis and hepatocellular carcinoma over time. Liver-elastography (LE) is a non-invasive, safe, and feasible ultrasound method to determine liver stiffness. Usually, this examination is performed sober and in strict inspiratory hold to optimize the results. However, the influence of food intake and respiration on these results in Fontan patients is unclear. To optimize the implementation for this examination especially in children, the effects of food intake and breathing maneuvers on liver stiffness in patients with Fontan circulation were investigated. Methods: For this study, 25 Fontan patients (group 1) and 50 healthy volunteers (group 2) were examined. Liver stiffness was measured by LE before food intake and 15, 30, 45, 60, 90, 120, 150 and 180 minutes after ingestion of a standardised meal (600kcal), each time in maximal inspiration and expiration. The study was reviewed and approved by the responsible ethics committee. Results: In group 2 there was a significant increase in liver stiffness after food intake at T15, T30 and T45 during inspiration (T0=4.0kPa vs T15=4.9kPa; T0=4.0kPa vs T30=4.9kPa; T0=4.0kPa vs T45=4.3kPa), as well as during expiration at T15 and T30 (T0=4.5kPa vs T15=5.1kPa; T0=4.5kPa vs T30=4.9kPa). Whereas in group 1 liver stiffness did not differ significantly at any time. Respiration in group 2 differed significantly at T0 (insp=3.97kPa vs. exp=4.48kPa). In group 1, there was no significant difference between the respiratory phases at any point. Conclusion: With these results we could demonstrate for the first time that in Fontan patients the time of food intake and respiration has no clinical significance for the values obtained in LE. Consequently, liver elastography for Fontan patients is reliable independently of food intake and breathing maneuvers and can also be performed on younger patients, who are unable to follow breathing commands or longer fasting periods, without any impairment of the results. These results should encourage a routine use of LE in the follow-up of Fontan patients.